2021
DOI: 10.22271/oral.2021.v7.i1f.1159
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient and parental preference between nitrous oxide sedation and conventional behavior management technique for dental treatment: A randomized crossover study

Abstract: Aim: To Compare patient and parental preference between nitrous oxide sedation and conventional behaviour management technique for dental treatment. Material and Methods: This cross-over split mouth study design was performed on 30 children (6-12 years old) who require a bilateral treatment involving inferior alveolar nerve block. 15 children were enrolled in a group A & 15 children in a group B. Thereafter, the outcome of preference of technique was assessed by parent and child after both techniques were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…According to AAPD guidelines (2020), the use of a pulse oximeter is recommended throughout the procedure to measure physiological parameters. 21 In the present study, we used a pulse oximeter throughout the procedure and observed no adverse changes in physiological parameters.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…According to AAPD guidelines (2020), the use of a pulse oximeter is recommended throughout the procedure to measure physiological parameters. 21 In the present study, we used a pulse oximeter throughout the procedure and observed no adverse changes in physiological parameters.…”
Section: Discussionmentioning
confidence: 54%
“… 17 , 18 Studies emphasize that N 2 O IHS is the most efficient and safest aid in managing child patients, even in long dental procedures, with increased acceptance by patients and parents. 2 , 19 21 In the present study, we used N 2 O IHS to manage dental anxiety in children.…”
Section: Discussionmentioning
confidence: 99%